Employee Satisfaction Analysis of Emerald Bank Indonesia Branch - Andina, Meity; Hidajat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2017)
Abstract – Problems that arise in the Emerald Bank of which is that firms face greater difficulties in obtaining the necessary human resources to meet individual goals and objectives of the company. The existence of employee dissatisfaction is characterized by a lack of positive respond to staff’s achievements. It may affect their loyalty, dedication and honesty if no proper appreciation from the institution. Purpose - This study was to examine the relationship of job characteristics toward job satisfaction in Emerald Bank Indonesia. Therefore, a correlational study is engaged to identify the relationship between significant factors (as independent variable) and the problem (as dependent variable). The data collection refers to the observation of such relationship was using a quantitative method. The reason of using quantitative method due to its allow statistical analyzes to verify the data collected are reliable and valid. Questionnaire has been sent to 57 respondents were employed as an instrument for this study. Findings – the outcomes of this study came with eight factors of job characteristics which are workplace environment, supervision, cooperation from peers, work discrimination, employee acceptance, work allocation, job security, and remuneration. Based on the observations result, this study has formulated HRM implementation practices focusing in these objects: 1.Supervisor improvement; 2.Situational leadership; 3.Carrier Development; 4.Benefit equality; 5.Management improvement (rewards and recognition); 6.Peer to peer attachment & cross division; 7.Promotion; 8.Workstation rotation.Keywords: job satisfaction, effectiveness of supervision, employee acceptance, work allocation, cross division, rewards and recognizing